2014
DOI: 10.1007/s13277-014-1753-z
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of serum vascular endothelial growth factor and matrix metalloproteinase-3 in patients with oral squamous cell carcinoma

Abstract: Vascular endothelial growth factor (VEGF) is known as a fundamental regulator of angiogenesis that accelerates cellular proliferation, vascular permeability, and endothelial cell migration and is an inhibitor of apoptosis. Extracellular matrix degradation by matrix metalloproteinase (MMP) is necessary for endothelial cell proliferation, migration, and metastasis. Accordingly, the objective of the present study was to determine the circulating levels of VEGF and MMP3 and their relation in patients with oral squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…VEGF is a pro‐angiogenic factor in tumor angiogenesis, which is released by neoplastic cells, infiltrating inflammatory cells, endothelial cells, and fibroblasts . In fact, we detected VEGFA protein expression in the cytoplasm of parenchymal and stromal cells in OSCC samples, including fibroblasts and endothelial cells, and similar findings have been reported in other study .…”
Section: Discussionsupporting
confidence: 91%
“…VEGF is a pro‐angiogenic factor in tumor angiogenesis, which is released by neoplastic cells, infiltrating inflammatory cells, endothelial cells, and fibroblasts . In fact, we detected VEGFA protein expression in the cytoplasm of parenchymal and stromal cells in OSCC samples, including fibroblasts and endothelial cells, and similar findings have been reported in other study .…”
Section: Discussionsupporting
confidence: 91%
“…More recently, elevated plasma level of MMP9 is proved to be valuable to identify metastatic phenotype and as treatment monitor in patients with OSCC (Patel, Shah, Shukla, Shah, & Patel, 2007). Additionally, up-regulated MMP3 has been identified to play a potential role in the pathogenesis of OSCC and activated MMP3 might contribute to regulate angiogenesis that is a key process of tumor metastasis (Andisheh-Tadbir et al, 2014). Consistent with previous studies, result of function enrichment in the present study demonstrated that the three MMPs were involved in tumor metastasis of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increase expression of MMP-3 correlated with the stage of tumour suggesting the participation of this enzyme in the pathogenesis and progression of the disease. 41,42 In an attempt to asses where MMP-3 was stored following its synthesis, we analysed the presence of the protein in three different preparations: in conditioned media, in cell lysates without trypsin treatment and in cell lysates obtained following trypsin treatment. The highest level of the enzyme was found in the cell lysates without trypsin treatment preparation.…”
Section: Discussionmentioning
confidence: 99%